2007
DOI: 10.4049/jimmunol.179.2.1254
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Anti-Inflammatory Effects of Myeloid Cell Adenosine Receptor A2a Stimulation in Lipopolysaccharide-Induced Lung Injury

Abstract: To determine the role of the adenosine receptor A2a in a murine model of LPS-induced lung injury, migration of polymorphonuclear leukocytes (PMNs) into the different compartments of the lung was determined by flow cytometry, microvascular permeability was assessed by the extravasation of Evans blue, and the release of chemotactic cytokines into the alveolar airspace was determined by ELISA. Measurements were performed in wild-type and A2a gene-deficient mice (A2a−/−). To differentiate the role of A2a on hemopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 66 publications
4
120
2
4
Order By: Relevance
“…In ischemia reperfusion models, the use of A 2A receptor agonists resulted in a decrease in macrophage activation and adhesion molecular expression on endothelial cells, blockage of endothelial-neutrophil interactions, and attenuation of vascular derangement (11,12,(17)(18)(19)(20)(21). The administration of the A 2A receptors agonist CGS-21680 has been shown to ameliorate lung injury in animal models of ischemia and reperfusion (12,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ischemia reperfusion models, the use of A 2A receptor agonists resulted in a decrease in macrophage activation and adhesion molecular expression on endothelial cells, blockage of endothelial-neutrophil interactions, and attenuation of vascular derangement (11,12,(17)(18)(19)(20)(21). The administration of the A 2A receptors agonist CGS-21680 has been shown to ameliorate lung injury in animal models of ischemia and reperfusion (12,17).…”
Section: Discussionmentioning
confidence: 99%
“…The A 2A R expressed on leukocytes and lung displays high affinity for adenosine (8). Several studies have shown that activation of A 2A receptor is protective against ischemia/reperfusion injury by decreasing the expression of endothelial adhesion molecules and the production of cytokines and reactive oxygen species (17)(18)(19)(20)(21). We thus hypothesized that a pharmacologic intervention with an A 2A R agonist protects the lung from injury in a two-hit model of HSR followed by mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Each type of adenosine receptor exhibits a distinct pharmacological and physiological profile [14]. Adenosine receptors A2a and A2b have been recognized as important mediators in inflammatory models [15,16]. Additionally, Schingnitz et al [17] showed that LPS treatment induced Adora2b transcription and corresponding protein expression in in vivo and in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified CD39 and CD73, both rate-limiting enzymes for the generation of extracellular adenosine, as critical mediators in pulmonary inflammation (16,17). In addition, activation of ARs A2a and A2b has been demonstrated to attenuate organ damage in LPS-and ventilator-induced lung injury (18,19).…”
mentioning
confidence: 99%